Staff satisfaction in the functionalisation of psychiatric in-patient care - Shishir Regmi; Debbie Cooper; Maxine O’Brien; Susmit Roy; Tongeji E. Tungaraza; Surendra P. Singh; Nilamadhab Kar (Mental Illness, 2012)
In many UK mental health services, inpatient psychiatric care is being separated from community care by having dedicated inpatient medical team. We evaluated staff satisfaction in this functionalised in-patient care. A survey was conducted amongst multidisciplinary staff from various teams using a questionnaire survey. On an average 14.3% of staff returned a satisfactory response for functionalisation, 57.3% had unsatisfactory response and others were undecided or perceived no change. There was no difference in responses amongst age, gender and professional groups. Mean scores of all groups were within unsatisfactory domain; however community staff compared to in-patient staff and staff with more than 5 years of experience compared to those with 1-5 years of experience returned significantly more unsatisfactory responses regarding functionalisation. Many positive and negative aspects of functionalisation were raised. The results of this evaluation suggest the need for further studies on the effectiveness of inpatient functionalisation. Short and long term clinical outcomes and the satisfaction of the patients should also be studied.